Regulation of Early Plant Development by Red and Blue Light: A Comparative Analysis Between Arabidopsis thaliana and Solanum lycopersicum - Spaninks, Kiki; van Lieshout, Jelmer; van Ieperen, Wim; Offringa, Remko (Frontiers in Plant Science, 2020)
In vertical farming, plants are grown in multi-layered growth chambers supplied with energy-efficient LEDs that produce less heat and can thus be placed in close proximity to the plants. The spectral quality control allowed by LED lighting potentially enables steering plant development towards desired phenotypes. However, this requires detailed knowledge on how light quality affects different developmental processes per plant species or even cultivar, and how well information from model plants translates to horticultural crops. Here we have grown the model dicot Arabidopsis thaliana (Arabidopsis) and the crop plant Solanum lycopersicum (tomato) under white or monochromatic red or blue LED conditions. In addition, seedlings were grown in vitro in either light-grown roots (LGR) or dark-grown roots (DGR) LED conditions. Our results present an overview of phenotypic traits that are sensitive to red or blue light, which may be used as a basis for application by tomato nurseries. Our comparative analysis showed that young tomato plants were remarkably indifferent to the LED conditions, with red and blue light effects on primary growth, but not on organ formation or flowering. In contrast, Arabidopsis appeared to be highly sensitive to light quality, as dramatic differences in shoot and root elongation, organ formation, and developmental phase transitions were observed between red, blue, and white LED conditions. Our results highlight once more that growth responses to environmental conditions can differ significantly between model and crop species. Understanding the molecular basis for this difference will be important for designing lighting systems tailored for specific crops.